If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-7p + -3) = 10(p + -3) Reorder the terms: -1(-3 + -7p) = 10(p + -3) (-3 * -1 + -7p * -1) = 10(p + -3) (3 + 7p) = 10(p + -3) Reorder the terms: 3 + 7p = 10(-3 + p) 3 + 7p = (-3 * 10 + p * 10) 3 + 7p = (-30 + 10p) Solving 3 + 7p = -30 + 10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10p' to each side of the equation. 3 + 7p + -10p = -30 + 10p + -10p Combine like terms: 7p + -10p = -3p 3 + -3p = -30 + 10p + -10p Combine like terms: 10p + -10p = 0 3 + -3p = -30 + 0 3 + -3p = -30 Add '-3' to each side of the equation. 3 + -3 + -3p = -30 + -3 Combine like terms: 3 + -3 = 0 0 + -3p = -30 + -3 -3p = -30 + -3 Combine like terms: -30 + -3 = -33 -3p = -33 Divide each side by '-3'. p = 11 Simplifying p = 11
| 3t+8(2t-6)=2+14 | | -p/2=4/3 | | -2/2/3+d/6=2/3 | | -92=6x+4(x+2) | | 3(b-21)+3(b-4)=27 | | 1-5(2)= | | -5(2)+1= | | 34-9p=-3 | | -7x-57x(6+1002)=12x | | 15h-=6 | | -12n-20= | | 3a+2b-8a+b= | | -3(W+2)=2(W+6)+7 | | 4x+1=7x+8 | | 4x-7+4x=9 | | 2n-3(11n+3)=-5(7n-3) | | 7(Y-1)-8=-4(-4Y+6)-3Y | | 0.25x+2=11 | | 3X-42=8(X+1) | | 8-0.5y=-6 | | 5(-3+12x)=-3x+6(11x-1) | | 6+2x-x-3-5x= | | 6-r=-6(r-1) | | -6(-1-7m)=6-5m | | n+1+4n=-9 | | 5-0.5x=9 | | -6m-m=14 | | -16x-12=36-4x | | q=180/12 | | 5x+4*-50=100 | | 70=10(3t-2) | | 3.9m-3-3.9m-9= |